Efektivitas Peran Dewan Pengawas Syariah Dalam Meminimalkan Risiko Kepatuhan di Bank Syariah di Indonesia - Y, Yusra; N, Nurnarsrina; Febriyani, Nola; Huda, Nurul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Islamic banks have a responsibility to ensure that every product, service, and operational activity is in accordance with sharia principles. Non-compliance with sharia principles not only risks legal sanctions but can also damage the bank's reputation and reduce customer trust. In this context, the Sharia Supervisory Board (SSB) plays a central role as an independent supervisor tasked with ensuring compliance. This study aims to evaluate the effectiveness of the SSB's role in mitigating compliance risks in Islamic banks. The study will analyze the extent to which the SSB is involved in the supervision process, the obstacles faced in carrying out its duties, and recommendations for improving the functionality of the SSB. Using a descriptive qualitative approach, data will be obtained through literature studies, interviews with SSB members, and case studies of several Islamic banks in Indonesia. The results of this study are expected to provide a comprehensive picture of the role of the SSB in managing compliance risks and become a consideration for stakeholders in improving the governance of Islamic banks. In addition, the recommendations produced can help optimize the role of the SSB to be more effective in maintaining the integrity of the Islamic financial system in Indonesia.